2022
DOI: 10.2463/mrms.rev.2021-0063
|View full text |Cite
|
Sign up to set email alerts
|

Safety for Human MR Scanners at 7T

Abstract: After introduction of the first human 7 tesla (7T) system in 1999, 7T MR systems have been employed as one of the most advanced platforms for human MR research for more than 20 years. Currently, two 7T MR models are approved for clinical use in the U.S.A. The approval facilitated introduction of the 7T system, summing up to around 100 worldwide. The approval in Japan is much awaited. As a clinical MR scanner, the 7T MR system is drawing attention in terms of safety.Several large-sized studies on bioeffects hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Studies have reported a possible increase in bio‐effects and adverse events related to radiofrequency‐induced tissue heating and metallic implants compared to 3 T MR‐scans 19,20 . High field related side effects were not reported in this study (dizziness, motion disturbances, nausea) 19,20 .…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…Studies have reported a possible increase in bio‐effects and adverse events related to radiofrequency‐induced tissue heating and metallic implants compared to 3 T MR‐scans 19,20 . High field related side effects were not reported in this study (dizziness, motion disturbances, nausea) 19,20 .…”
Section: Discussionmentioning
confidence: 50%
“…Studies have reported a possible increase in bio‐effects and adverse events related to radiofrequency‐induced tissue heating and metallic implants compared to 3 T MR‐scans 19,20 . High field related side effects were not reported in this study (dizziness, motion disturbances, nausea) 19,20 . In the 450 7 T MR‐scans we have performed to date, we rarely encountered non‐compatible implants (all patients undergo safety screening with a questionnaire and magnetometer) or severe side effects.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…159 Although there is growing literature on the safety of surgical implants at higher field strengths, [160][161][162][163] there are not yet any definitive guidelines for imaging patients with nonmagnetic standard titanium plates placed during HGG resections, which has limited the clinical integration of 7T MRS thus far. 164 It is important to perform additional testing and develop explicit guidance on whether surgical implants are safe at higher fields. 165 The increased use of 7T MRS to scan patients in this category would allow longitudinal evaluations of patients with HGG at different phases of treatment, including postoperative follow-ups during radiation therapy, which have largely been confined to lower field strengths but ought to be expanded more widely to higher field strengths.…”
Section: Future Clinical Directionsmentioning
confidence: 99%
“…This review highlights the advantages of 7T neuroimaging for anatomical visualization, presents a brief review of 7T neurochemical measurements and technical issues, and summarizes the principal difficulties of 7T imaging. We recommend other reviews for information on 7T-related safety issues (13)(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%